Understanding the role of food matrix on the digestibility of dairy products under elderly gastrointestinal conditions. (November 2020) - Hernández-Olivas, Ever; Muñoz-Pina, Sara; Sánchez-García, Janaina; Andrés, Ana; Heredia, Ana
Graphical abstract: Highlights: Proteolysis is the dairy-macronutrient affected the most by GI elderly conditions. Food structure (liquid or solid) is a key-determinant of dairy digestibility. Leucine reduction by up to 44% in milk digested under elderly GI conditions. Calcium, vitamin A and D3 bioaccessibility highly depends on the dairy matrix. Abstract: This study aimed to evaluate the effect of some elderly in vitro gastrointestinal (GI) conditions on proteolysis and lipolysis extent, calcium, vitamins A and D bioaccessibility and lactose release in milk, yogurt, fresh and aged cheeses. To evaluate the impact of the some oral, gastric and intestinal disorders appearing with ageing on dairy digestion, three in-vitro elderly models were applied (E1 (oral altered conditions), E2 (oral and gastric altered conditions) and E3 (oral, gastric and intestinal altered conditions)) plus a healthy adult one as control. Proteolysis extent was significantly affected by elderly GI alterations (p < 0.05) (around 40% of reduction compared to control), being fresh and aged cheese proteolysis the most affected with an important descrease in leucine release (18 and 25%, respectively). Calcium, vitamins A and D3 bioaccesibility and lactose release seemed not to be highly compromised in these models of elderly conditions; however, the micronutrients bioaccessibility was very dependent on dairy matrix's structure. Finally, the amount of the lipid hydrolyzed fraction of cheeses is not influenced in the investigated models.